THE MAIN PROBLEMS OF THE DEVELOPMENT OF SERVICE ACTIVITIES IN THE HOTELIER AND WAYS TO ELIMINATE THEM - Khamitov Mubin Khabibzhonovich (International Journal of Business, Law and Political Science, 2024)
General Background: The rapid advancement of digital technology has reshaped the global hotel industry, enhancing service quality and operational efficiency to meet evolving customer expectations. Specific Background: In Uzbekistan, efforts to align the hotel sector with global standards have intensified under the "Digital Uzbekistan – 2030" strategy and the "Travel Through New Uzbekistan" initiative, aiming to attract both local and international tourists. Knowledge Gap: However, Uzbekistan’s hotel industry faces significant barriers, such as inadequate service quality, lack of skilled personnel, outdated regulatory standards, and limited integration of digital infrastructure. Aims: This study investigates the current challenges and prospects for sustainable development and digital transformation in Uzbekistan’s hotel sector, focusing on innovative approaches to improve service quality and operational effectiveness. Results: Findings indicate that although Uzbekistan's hotel industry lags in digital adoption compared to sectors like finance and manufacturing, there is a high demand for digital transformation to enhance customer service, particularly through digitized booking, integrated management systems, and expanded digital communication channels. Novelty: This study provides a comprehensive analysis of Uzbekistan’s unique barriers and opportunities, identifying specific digital strategies that can enhance competitiveness and align with global tourism standards. Implications: Integrating digital systems in the hospitality sector can increase customer satisfaction, attract international visitors, and support the broader tourism objectives of New Uzbekistan. By adopting best practices from international benchmarks, Uzbekistan’s hotel industry could strengthen its market position and contribute to sustainable economic development in the tourism sector.